CASE STUDY REHABILITATION TENORRHAPHY ACHILLES TAPING BY NEUROMUSCULAR (Fiep Bulletin - online, 2013)
The Achilles tendon is the completion of three muscles, gastrocnemius, soleus and plantaris who in turn form the sural triceps. This muscle group is attached to the tendon which is inserted into the posterior surface of the calcaneus bone at the heel, are responsible for the plantar flexion of the foot. The Achilles tendon rupture is increased by the high rate of physical inactivity and increased people doing sport eventually, but with a lower index are athletes. People with this type of injury manifest pain in the back of your neck stand them impossible to perform plantar flexion. Factors have been identified that will enhance it more often this tendon rupture such as the failure to conduct a proper warm up before any sport and chronic degenerative diseases of the body. Although in some cases surgery is performed, the treatment is more tenorrhaphy choice, that is to make an end of suture which has been ruptured tendon. The mechanism of action of NEUROMUSCULAR TAPING circulatory level causes an increase in the subcutaneous space between perilymphatic capillaries, the capillaries and different receivers afferent and efferent, and immediately reducing the pressure of mechanoreceptors, pain level generates a reduced nociceptors pressure reducing pain levels almost immediately.
Keywords: Tendon; surgery; rehabilitation; neuromuscular taping; mechanoreceptors